Liquid Chromatographic Enantioseparations Utilizing Chiral Stationary Phases Based on Crown Ethers and Cyclofructans - Róbert Berkecz; Gábor Németi; Antal Péter; István Ilisz (Molecules, 2021)
Natural compounds can exist in different forms, where molecules possessing chirality play an essential role in living organisms. Currently, one of the most important tasks of modern analytical chemistry is the enantioseparation of chiral compounds, in particular, the enantiomers of compounds having biological and/or pharmaceutical activity. Whether the task is to analyze environmental or food samples or to develop an assay for drug control, well-reproducible, highly sensitive, stereoselective, and robust methods are required. High-performance liquid chromatography best meets these conditions. Nevertheless, in many cases, gas chromatography, supercritical fluid chromatography, or capillary electrophoresis can also offer a suitable solution. Amino acids, proteins, cyclodextrins, derivatized polysaccharides, macrocyclic glycopeptides, and ion exchangers can serve as efficient selectors in liquid chromatography, and they are quite frequently applied and reviewed. Crown ethers and cyclofructans possessing similar structural characteristics and selectivity in the enantiodiscrimination of different amine compounds are discussed less frequently. This review collects information on enantioseparations achieved recently with the use of chiral stationary phases based on crown ethers or cyclofructans, focusing on liquid chromatographic applications.